Detection of Single Pt Nanoparticle Collisions by Open‐Circuit Potential Changes at Ag Ultramicroelectrode. (14th February 2016) - Mun, Seon Kyu; Shin, Changhwan; Kwon, Seong Jung
Abstract : Abstract : Single platinum (Pt) nanoparticle (NP) collisions were investigated with open‐circuit potential (OCP) using a silver (Ag) ultramicroelectrode (UME). The Ag UME showed higher sensitivity to single Pt NP detection by the OCP method than gold (Au) UME. The detection of ~2 nm radius Pt NP collisions was carried out successfully using Ag UME. The magnitude of the potential step and collision frequency for the single Pt NP collision on Ag UME was investigated and compared with those of the previous work done on Au UME.